AKSELERASI PENDIDIKAN TINGGI DALAM MENJAWAB KEBUTUHAN PENDIDIKAN DASAR DAN MENENGAH - H Bahaking Rama (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2011)
Education has been an important medium of deve-loping human civilization. Qualified human resource is, of course, a result of education; one of them is higher education. Higher education, as formal educational institution, should play an important role to answer the need of primary and secondary education, one of them is professional teachers. The fact shows that the alumni of teacher trai-ning higher education are great in number, nevertheless, only a small number of them may be classified as qualified, most need prerequisites before teaching in the classrooms. This paper will deeply discuss the importance of education at the primary and secondary levels, and how the higher educational institutions support these by providing more qualified educators.